The Value of Enterprise Architecture in Malaysia Enterprise-From the Perspective of CIO - Ngai, Kah Seng (2015)
This study was aimed at establishing the value of enterprise architecture in Malaysian business enterprises as perceived and experienced by the Chief Information Officers (CIOs) of a total of 7 enterprises. The research design was qualitative given that the study was aimed at describing and understanding, rather than explaining the way enterprise architecture is used with the Malaysian enterprises to deliver business values. Data was collected through a semi-structured interview that involved respondents who were serving as Chief Information Officers or Directors of Informatics within the Malaysian enterprises. After each and every interview session, the researcher transcribed all audio cassettes and included the same in the transcripts. The key finding of the study included the fact that EA is critical in terms of providing business enterprises with a guide to delivering different business values using IT infrastructure. Organization structure and complexity was also found to influence the top management’s decision on whether EA investments are worthwhile in addition to dictating whether the implementation of EA can allow the IT organization to adopt a manner of operation that is compliant with the overall business objectives. The study concludes that CIOs or persons charged with the duty to oversee IT infrastructure should ensure constant improvement and more alignment of the IT organization and adventures to the corporate needs.